The Debt Crisis: Lessons of the 1980s - John Williamson (Asian Development Review, 1991)
It is now over nine years since Mexico found itself unable to service its debt in August 1982, and was forced into declaring a moratorium that precipitated what quickly became known as the debt crisis. A vast literature has emerged since then on the causes of that crisis, on apportioning responsibility for its occurrence or persistence, and on prescribing remedies for ending it…